Expression and function of the protein tyrosine phosphatase receptor J (PTPRJ) in normal mammary epithelial cells and breast tumors. - Chanel E Smart; Marjan E Askarian Amiri; Ania Wronski; Marcel E Dinger; Joanna Crawford; Dmitry A Ovchinnikov; Ana Cristina Vargas; Lynne Reid; Peter T Simpson; Sarah Song; Christiane Wiesner; Juliet D French; et al. (PLoS ONE, 2012)
The protein tyrosine phosphatase receptor J, PTPRJ, is a tumor suppressor gene that has been implicated in a range of cancers, including breast cancer, yet little is known about its role in normal breast physiology or in mammary gland tumorigenesis. In this paper we show that PTPRJ mRNA is expressed in normal breast tissue and reduced in corresponding tumors. Meta-analysis revealed that the gene encoding PTPRJ is frequently lost in breast tumors and that low expression of the transcript associated with poorer overall survival at 20 years. Immunohistochemistry of PTPRJ protein in normal human breast tissue revealed a distinctive apical localisation in the luminal cells of alveoli and ducts. Qualitative analysis of a cohort of invasive ductal carcinomas revealed retention of normal apical PTPRJ localization where tubule formation was maintained but that tumors mostly exhibited diffuse cytoplasmic staining, indicating that dysregulation of localisation associated with loss of tissue architecture in tumorigenesis. The murine ortholog, Ptprj, exhibited a similar localisation in normal mammary gland, and was differentially regulated throughout lactational development, and in an in vitro model of mammary epithelial differentiation. Furthermore, ectopic expression of human PTPRJ in HC11 murine mammary epithelial cells inhibited dome formation. These data indicate that PTPRJ may regulate differentiation of normal mammary epithelia and that dysregulation of protein localisation may be associated with tumorigenesis.